2022
DOI: 10.3389/fmed.2021.759605
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Gene Expression Profiling Identifies Programmed Cell Death Ligand-1 Centered Immunologic Subtypes of Oral and Squamous Cell Carcinoma With Favorable Survival

Abstract: ObjectiveThis study aimed to identify the programmed death ligand-1 (PDL1, also termed as CD274) and its positively correlated immune checkpoint genes (ICGs) and to determine the immune subtypes of CD274-centered ICG combinations in oral and squamous cell carcinoma (OSCC).Materials and MethodsFirstly, the 95 ICGs obtained via literature reviews were identified in the Cancer Genome Atlas (TCGA) database in relation to OSCC, and such 88 ICG expression profiles were extracted. ICGs positively correlated with CD27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 62 publications
2
9
0
Order By: Relevance
“…Combining targeted medicine that is aimed at the microenvironment for cancer with conventional treatment such as chemotherapy and radiotherapy might enhance tumor patient’s efficacy in the practical field. Researchers anticipate the development of additional therapies to tackle checkpoint components would enhance the clinical results for patients and eventually lead to cancer eradication [ 24 , 25 , 31 ]. The majority of findings for elderly and ccRCC patients, whether in localized or distant areas during the ICI and non-ICI era, are still in their early stages [ 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combining targeted medicine that is aimed at the microenvironment for cancer with conventional treatment such as chemotherapy and radiotherapy might enhance tumor patient’s efficacy in the practical field. Researchers anticipate the development of additional therapies to tackle checkpoint components would enhance the clinical results for patients and eventually lead to cancer eradication [ 24 , 25 , 31 ]. The majority of findings for elderly and ccRCC patients, whether in localized or distant areas during the ICI and non-ICI era, are still in their early stages [ 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…We included coding genes (19,658 genes) from fragments per kilobase of exon per million mapped (FPKM). In the study of gene expression, these were matched with the ICI genes that were obtained from new ICI databases (the checkpoint therapeutic target database (CKTTD) and recently published new ICI genes list) [ 24 , 25 ]. For validation of our gene signature, we used the gene expression profile of 604 ccRCC patients from the GEO database (GSE167093) [ 26 ].…”
Section: Patient’s Methods and Materialsmentioning
confidence: 99%
“…Survival analysis showed that most ICs, including BTLA, were significantly associated with OS. Combinations such as low PD-L1/ low BTLA and high CD8alpha/ low BTLA were predictive of a favorable prognosis in OSCC [ 84 ]. Similarly, Weber et al performed a comparative analysis of IC expression in OSCC.…”
Section: Btla In Cancermentioning
confidence: 99%
“…JUN-dependent immune checkpoint expression was inhibited by blocking CDK1/2/5 in pancreatic cancer in response to interferon gamma [ 11 ]. Targeting immune checkpoints by blocking co-inhibitory molecules or activating co-stimulatory molecules has emerged as one of the important options in cancer treatment [ 18 ]. Microsatellite instability (MSI) and tumor mutational burden (TMB) function as predictive biomarkers for favorable outcomes of cancer immunotherapy [ 19 ].…”
Section: Introductionmentioning
confidence: 99%